Morphological transition of Helicobacter pylori adapted to water. (October 2017) - Fernandes, Ricardo M; Silva, Hélder; Oliveira, Ricardo; Almeida, Carina; Azevedo, Nuno F; Vieira, Maria J
Aim: This study aims to investigate the morphological transition of Helicobacter pylori during adaptation to water.Materials & methods: Different strains were adapted to water. Changes regarding cultivability and cellular morphology were recorded. Expression of 11 genes involved in H. pylori morphological changes was evaluated by real-time PCR.Results: H. pylori presented increased cultivability in water after adaptation. The permanent loss of the spiral shape was observed, but no transition into coccoid form has occurred. Expression levels of genes involved in peptidoglycan assembly of H. pylori 26695 have shown significant changes between adapted and nonadapted strains.Conclusion: Adaption to water favors the culturable phenotype and the morphological transition to the rod shape, into a process that implicates the peptidoglycan turnover.